Migrations of Jesuits Within and Outside the Order’s Polish Province and Their Educational Consequences in the Second Half of the 17th Century - Seryakov, Sergiy (Sensus Historiae, 2024)
The article examines the issue of migrations of the Jesuits of the Polish Province and their educational consequences in the second half of the 17th century, which has not been sufficiently studied in historiography. The author emphasizes that since 1648, under the influence of the military factor, the tendency towards personnel self-suffuciency of the Polish Province was replaced by numerous Jesuit migrations, which reached the largest scale during the Deluge period. The resulting disorder in the formation of the personnel of the Polish Province had a negative impact on the education of teachers in its eastern centres—due to the deficite of magisters who had passed the necessary stages of formation, young Jesuits with gaps in intellectual training were often involved in teaching. This negative phenomenon was partly compensated by the presence of emigrant teachers, who studied and taught abroad. Such an experience ended the intellectual and cultural isolation of the Polish Province and positively influenced the creative and career path of the emigrants.